Design of Electromagnetic Shielding Textiles Based on Industrial‐Grade Multiwalled Carbon Nanotubes and Graphene Nanoplatelets by Dip‐Pad‐Dry Process. Issue 15 (17th January 2022) - Sousa, Ana R.; Matos, Renata; Barbosa, José R. M.; Ferreira, João; Santos, Gilda; Silva, Augusta; Morgado, José; Soares, Patrícia; Bunyaev, Sergey A.; Kakazei, Gleb N.; Vilarinho, Rui; Soares, Olívia Salomé; et al.
Abstract : Textile‐based shields are one of the most used solutions for electromagnetic interference (EMI) shielding in the radiofrequency range for several applications, such as personal protection, military, and aircraft. Herein, EMI textile shields are produced based on knitted cotton textile substrates (Jersey and American Fleece) coated with industrial‐grade multiwalled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs). An easy and scalable dip‐pad‐dry process is used to fabricate the textile‐based shields. The shielding effectiveness (SE) is evaluated over the frequency range of 5.85–18 GHz. The MWCNT‐coated American Fleece fabric presents the highest EMI shielding, with an average SE of ≈35.6 dB, which corresponds to an excellent classification for general use applications. Additionally, the electrical properties of the carbon nanomaterials and the thickness of the shields reveal to be correlated with an EMI shielding process mostly through radiation absorption mechanism. Numerical simulations are used to further assist in a thorough investigation regarding the influence of the electrical properties of the nanomaterials on the SE of the resulting coated fabrics. Abstract : Electromagnetic interference (EMI) textile shields are produced based on knitted cotton textile substrates (Jersey and American Fleece) coated with industrial‐grade multiwalled carbon nanotubes and graphene nanoplatelets over the frequency range of 5.85–18 GHz. An average SE of ≈35.6 dB is achieved, which corresponds to an excellent classification for general use applications.